Metaplasia-dysplasia-carcinoma sequence in cases of cholelithiasis: a histopathological study - Devi, Sabari; Kalita, Deep Jyoti (International Journal of Medical Research and Review, 2016)
Introduction: Cholecystectomy is one of the most common abdominal surgeries performed across the world and in majority of the cases, is performed due to gall stones. The pathological changes related to gallstone formation are still the focus of intensive research. Presumably long standing gall stones produces a series of changes in the mucosa as a result of constant irritation, trauma and chronic inflammation. Aim of the study: The aim of our study was to find out the prevalence and sequence of metaplasia, dysplasia and malignancy in cholecystectomy cases due to gall stones. Materials and methods: A total 682 cholecystectomy specimen removed due to gall stones were studied for a two year period from April 2014 to March 2016. Results: Majority of the patients were females (75.22%). The youngest case was 15 years and oldest was 70 years of age. Antral metaplasia was noted in 41.05%, intestinal metaplasia in 4.5%, dysplasia in 2.34% and neoplasia 0.88% of cases. Histological continuity between epithelial changes was seen in 55 cases. 8 cases had continuity of antral metaplasia, intestinal metaplasia and dysplasia. 4 cases showed continuity of intestinal metaplasia with dysplasia and carcinoma and 3 cases showed continuity of dysplasia and carcinoma have a relationship. Conclusion: Hence it is inferred that metaplasia, dysplasia and carcinoma have an inter-relationship. Histopathological examination hence should be given utmost importance in all cases of cholelithiasis for identifying metaplasia, dysplasia and carcinoma.